2000
DOI: 10.1007/bf02236867
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous polyposis of the colon with multiple lipomas of peritoneal folds and giant diverticulosis

Abstract: A case of multiple lipomatosis exclusively located in the colon is reported in a young male (33 years). It is characterized by a great number of lipomas with polyposis growth appearance, multiple lipomas of peritoneal folds, and giant diverticulosis probably caused by weakened areas of colonic wall induced by the lipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…From the 135 patients, 121 patients presented with a single diverticulum, 12 presented with a double GCD [6, 7, 22, 26, 29, 42, 44, 51, 61, 81, 84, 102], and 2 patients presented with multiple GCD [71, 93]. Most diverticula are found in the sigmoid 109/135 (81%).…”
Section: Resultsmentioning
confidence: 99%
“…From the 135 patients, 121 patients presented with a single diverticulum, 12 presented with a double GCD [6, 7, 22, 26, 29, 42, 44, 51, 61, 81, 84, 102], and 2 patients presented with multiple GCD [71, 93]. Most diverticula are found in the sigmoid 109/135 (81%).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore more compelling to associate increased submucosal adiposis in our patient with his colonic diverticuli considering the established effect of same adipose tissues on tougher tissues like aponeurosis in abdominal wall hernias. Whilst colonic diverticulosis is commoner in older patients like our patient, Brouland et al reported a large colonic diverticulum in a young male arising due to colonic mural weakness by multiple colonic lipomatosis [19].…”
Section: Discussionmentioning
confidence: 52%
“…2003). These infiltrative lesions usually occur in the small intestine or colon and may be associated with diverticulosis (Brouland et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In man, lipomatosis of the intestine causing an intestinal obstruction is extremely rare and of unknown aetiology (Catania et al 1995;Shenoy et al 2003). These infiltrative lesions usually occur in the small intestine or colon and may be associated with diverticulosis (Brouland et al 2000). Submucosal lipohyperplasia of the ileocaecal valve, although rarely encountered clinically in man, is a reasonably common autopsy finding, where even marked lipohyperplasia has remained subclinical (Tawfik and McGregor 1992).…”
Section: Discussionmentioning
confidence: 99%